Quality and marketable characteristics of highbush blueberry (Vaccinium corym- bosum L.) under the Kyiv region conditions - В. О. Сіленко; С. В. Марченко (Plant Varieties Studying and Protection)
In the article the authors present the results of the study biometric and qualitative characteristics of berries highbush blueberry varieties (Vaccinium corymbosum L.) in a specific soil and climatic conditions Forest-steppe of Ukraine (Kiev). Investigations were carried out on 11 varieties of American highbush blueberry. Phenological observations, biometric surveys, tasting score and biochemical analysis of the berries have been conducted during the growing season. By results of researches the group of early-ripening varieties includes Bluestar, Earliblue, Patriot, the middle-ripening – Jonne, Atlantis, Bluegold, Bluecrop, Chyk and late-ripening varieties – Amanda, Darrow, Toro. Duration of collecting period of ripe berries was lower (16 days) in varieties Bluestar, Earliblue, Jonne and Darrow. Berries were large sizes in the varieties of Darrow, Amanda, Jonne, in other varieties berries were medium size. By tasting score the berry of varieties Toro, Earliblue, Jonne and Darrow were the best. For biochemical parameters the better varieties were Amanda, Jonne and Earliblue.